2009
DOI: 10.1038/modpathol.2008.199
|View full text |Cite
|
Sign up to set email alerts
|

Hypermutation in mantle cell lymphoma does not indicate a clinical or biological subentity

Abstract: Mantle cell lymphoma is a prime example of a well-defined entity based on morphology, phenotype, genetics and also clinical features. Although most patients have an adverse clinical course, some have a better survival than others. The most consistently reported adverse prognostic parameter is a high mitotic rate. Recently, it has been shown that hypermutation in the immunoglobulin heavy-chain gene occurs in a subset of mantle cell lymphomas. It is, however, unclear whether the mutational status is stable over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The clinical significance of IGVH mutations in MCL is controversial. Most studies have shown no relationship to the outcome of the patients (28)(29)(30), whereas a tendency to longer survival of the hypermutated MCL has been observed in some series (30)(31)(32)(33). Most of these studies have used a cutoff of 2% to consider the tumor as hypermutated.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of IGVH mutations in MCL is controversial. Most studies have shown no relationship to the outcome of the patients (28)(29)(30), whereas a tendency to longer survival of the hypermutated MCL has been observed in some series (30)(31)(32)(33). Most of these studies have used a cutoff of 2% to consider the tumor as hypermutated.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] In all published series, the classification of MCL cases based on SHM status was based on the 2% identity cut-off from the closest IGHV germ line gene, following the example of CLL, where this cut-off proved to be an accurate prognosticator of patient survival. 20 This approach should be viewed with caution for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In fresh or fresh-frozen samples, PCR amplification of IGHV-IGHD-IGHJ rearrangements was performed using IGHV leader primers or consensus primers for the IGHV framework region (FR) 1 region along with appropriate IGHJ gene primers, as described previously 9,12,[15][16][17] or following the BIOMED-2 protocol. 23 In formalin-fixed, paraffin-embedded material, deparaffinization was done according to standard methods, and gDNA was extracted using the QIAamp tissue kit (QIAGEN) following the manufacturer's recommendations.…”
Section: Pcr Amplification Of Ighv-ighd-ighj Rearrangementsmentioning
confidence: 99%
See 2 more Smart Citations